Static and dynamic analysis of functionally graded magneto-electro-elastic plates and shells - Zhang, Shun-Qi; Zhao, Ya-Fei; Wang, Xiang; Chen, Min; Schmidt, Rüdiger (Composite structures, 2022)
Functionally graded magneto-electro-elastic (FG-MEE) plates and shells have great application potential in smart structures for vibration control, shape control and health monitoring. The precise modeling technique for multi-physics coupled problems is a big challenge. This paper develops a finite element (FE) model coupled with magneto-electro-elastic fields for static and dynamic analysis of FG-MEE plates and shells. The FE model is derived by using the first-order shear deformation hypothesis with consideration of linear multi-physics coupled constitutive equations. Eight-node quadrilateral plate/shell elements are proposed for FG-MEE structures, including five mechanical DOFs at each node, one electric and magnetic DOF at each MEE layer of elements. The model is first validated by MEE laminated plates and shells, later applied to parametric study of FG-MEE structures with functionally graded electric and magnetic properties.